Boosting soil health and crop nutrients with locally sourced biochar and compost in Sacramento urban agriculture - Gao, Si; Medina, Monique; Gonzalez-Ospina, Laura; Burce, Katrina; Burce, Kristina; Melbourne, Alfred (Frontiers in Sustainable Food Systems, 2025)
Urban agriculture is crucial for enhancing food security in densely populated areas, but maintaining soil health in these settings is key for long-term productivity. This study investigates the effects of locally produced compost and biochar amendments on soil health and plant nutrients at two urban farms in Sacramento, California, USA. Regionally sourced biochar was produced from pistachio shells, and the compost was made from on-site green waste, creating a closed-loop system that recycles organic materials back into urban soils. We hypothesized that the combined application of biochar and compost would increase soil water holding capacity and nutrient retention, leading to enhanced microbial activity and higher nutrient concentrations in corn compared to individual amendments. Field trials were established at both sites using the randomized complete block design with four treatments: control, compost applied at approximately 25 t ha−1 (equivalent to 10 Mg C ha−1), biochar at 12.5 t ha−1 (equivalent to 10 Mg C ha−1), and a compost-biochar mix (20 Mg C ha−1). Soil samples were collected during mid- and late-season, and analyzed for key physicochemical and microbial properties. Corn kernel nutrient concentrations were also measured. Over one growing season, results showed that biochar and compost-biochar mix treatments significantly increased soil water holding capacity, organic matter content, and cation exchange capacity, leading to better soil structure and nutrient retention. Soil nitrate (NO3−–N) and bioavailable phosphorus (P) were significantly higher in biochar-amended soils. The compost-biochar mix enhanced microbial metabolic activity and microbial community evenness, though overall microbial diversity remained stable. Corn kernels in biochar and compost-biochar treatments exhibited increased nutrient concentrations, particularly for P, Mg, Ca, and Fe. Overall, the compost-biochar combination treatment had the most significant impact on improving soil physicochemical properties, microbial responses, and the plant nutrient concentrations, demonstrating their cumulative benefits for urban soil health and crop nutrition. By utilizing locally sourced materials and recycling organic waste, this study demonstrates a resource-efficient approach to improving soil fertility at resource-limited urban farms. These practices have the potential to play a vital role in addressing food security challenges in urban communities, particularly those experiencing food insecurity, while promoting sustainable resource management.